Pengaruh Current Rasio Terhadap Laba Perusahaan Pada PT Unilever Indonesia Tbk - Rahmayanti, Irma (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2026)
The purpose of this study is to analyze the effect of the Current Ratio on the profit growth of PT Unilever Indonesia Tbk. The study used the company's annual financial report data for the period 2022–2024. The data collection method was carried out through financial report documentation accessed from the official website of the Indonesia Stock Exchange (www.idx.co.id). Descriptive analysis was used to assess the trend of the Current Ratio calculated by comparing current assets to 7 liabilities. The results show that the Current Ratio of PT Unilever Indonesia Tbk has a downward trend, which affects the company's ability to meet obligations and impacts the company's annual profit growth.